Synthesis of pentaerythritol ester lubricants from palm oil methyl ester for refrigeration system - Idrus, Nor Faeqah (2019)
Polyol ester-based lubricants have been introduced in HFCs refrigeration system to replace conventional mineral oil-based lubricants due to compatibility issue of miscibility and solubility between lubricant and refrigerant. Polyol ester specifically the pentaerythritol (PE) ester that has high viscosity is known to have good miscibility with HFCs refrigerant and can be synthesized from methyl ester of vegetable oils via transesterification reaction. This research began with the optimization of transesterification reaction between palm oil methyl ester with pentaerythritol to produce PE ester at various reaction conditions. Kinetics study was performed on the transesterification reaction using integral method. Subsequently, the physicochemical properties also miscibility and solubility test with HFC refrigerant of PE ester base oil were analyzed and compared with commercial polyol ester (POE) RL 68H for refrigeration system. The reaction parameters selected for the optimization study were reaction temperature from 140°C to 170°C, molar ratio of POME to PE from 4:1 to 5:1, vacuum pressure from 5 to 50 mbar, catalyst concentration from 0.5% to 1.5% w/w and stirring rate from 300 rpm to 900 rpm and the reaction conducted for 2 hours in a stirred batch reactor. The optimum conditions of transesterification reaction were found at 160°C, molar ratio reactants at 4.5:1, catalyst concentration at 1.25%, vacuum pressure at 10 mbar and stirring speed at 900 rpm with the highest composition of PE tetraester obtained at 36% w/w. The mechanism of transesterification reaction was modelled as four-steps consecutive and irreversible reactions. The use of excess POME and continuous removal of methanol via vacuum suppressed the backward reaction. The reaction rate constants predicted follows the sequence of k1>k2>k3>k4. However, the proposed reaction rate law model was only accurate for reaction of PE to PE monoester and reaction of PE monoester to PE diester of reaction pathways. The activation energies for four stepwise series reaction ranges from 49.02 kJ/mol to 181.59 kJ/mol and the highest activation energies was obtained from the reaction of PE triester to PE tetraester. This explains the difficulty in converting PE triester to tetraester. Finally, the PE ester was analyzed for its physicochemical properties and was compared with commercial refrigeration polyol ester (POE) RL 68H. The kinematic viscosity and density of PE ester were comparable with commercial POE. The pour point obtained was at -24°C which is slightly higher than commercial POE. Nevertheless, the PE ester was not completely miscible in refrigerant, HFC R134a. An appropriate surfact improve the miscibility and solubility of PE ester with HFC refrigerant.